Application of Project-Based Learning (PjBL) Model on Biodiversity Material to Foster Knowledge of Students at Takengon State Senior High School 6 - Kismayeni; Ibrahim; Nurul Akmal; Muhammad Ridhwan; Azwir (Jurnal Penelitian Pendidikan IPA, 2026)
Project-Based Learning (PjBL) is an active and innovative learning model that can improve students' understanding of complex concepts in biology. This study aims to analyze the application of the PjBL model in biodiversity material and its impact on the knowledge of 10th grade high school students. The research method used a quasi-experimental design with a pretest-posttest control group design. The research sample consisted of 55 students divided into two groups: an experimental group (28 students) using the PjBL model and a control group (27 students) using a conventional learning model. The results showed a significant difference between the learning outcomes of the experimental and control groups (p < 0.05). The average posttest score of the experimental group (85.2) was higher than that of the control group (74.6). The PjBL model proved to be effective in fostering students' knowledge of biodiversity through authentic and contextual learning experiences.